Carbon dioxide laser treatment in burn-related scarring: A prospective randomised controlled trial. Issue 6 (June 2019) - Douglas, Helen; Lynch, Jessica; Harms, Karl-Anton; Krop, Tadyn; Kunath, Lauren; van Vreeswijk, Christine; McGarry, Sarah; Fear, Mark W; Wood, Fiona M; Murray, Alexandra; Rea, Suzanne
Summary: Aim: To investigate the effect of ablative fractional CO2 laser (AFCO2 L) on burns scar appearance and dermal architecture at 6 weeks and up to 3-years post-treatment. Methods: Twenty adult patients with a burn-related scar were recruited. Inclusion criteria were a minimum scar area of 10 × 10 cm and Vancouver scar scale (VSS) score of >5 and ≥6 months since the time of injury. The region of scar was randomised to treatment/control zones. Treatment zones received 3 standardised laser treatments at 4- to 6-week intervals. All areas of scar received standard scar care. Outcome measures were recorded at baseline, 6-weeks post final treatment and up to 3 years post-treatment. Measures included blinded assessor VSS, Patient Scar Assessment Scale and histological tissue analysis. Results: Nineteen and nine patients completed the short- and long-term studies, respectively. Clinical results revealed improvement in all scar areas over time. There was a statistically significant improvement in pain and itch in the treatment zone compared to the control zone at 6 weeks. Histological data revealed a significant increase in medium-sized collagen fibres at 6 weeks relative to the control site. Sub-group analysis according to scar age revealed greater histological improvement following laser treatment in immature scars relative to more mature scar. Conclusions: Results demonstrate that 3 treatments of AFCO2 L significantly improve scar pain, itch and dermal architecture at 6 weeks post-treatment. Histological results suggest greater potential in treating immature scar. Further investigation into the timing of laser treatment could help assist treatment protocols.